Harlem Grown : how one big idea transformed a neighborhood - Hillery, Tony (A Paula Wiseman Book, Simon & Schuster Books for Young Readers, 2020)
"Once there was a lot full of trash. Now there is a lush, green farm. This is the story of Harlem Grown, a garden in New York City"--